Self-conductive organic quaternary ammonium lithium salt-based ultra-concentrated electrolyte for safe lithium metal batteries - Liu, Yijing; Qiao, Sibo; Hu, Jinrui; Guo, Fen; Bao, Lixia; Lin, Weichao; Xu, Xiao; Liu, Pengpeng; Kong, Weibo; Jia, Yuehan; Wang, Jiliang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •Self-conductive organic lithium salt with the ionic conductivity of 0.35 × 10−3 S cm−1 is prepared.•The quasi-solid electrolyte exhibits excellent thermal and electrochemical stability.•The SEI film formation mechanism has been investigated by molecular dynamics and XPS techniques.•The assembled Li|UC-QLi|NCM solid-state cell delivers an initial discharge capacity of 164.1 mAh/g.•The UC-QLi-based solid-state cell presents outstanding safety. Electrolytes used in lithium batteries (LBs) have been the subject of considerable research interest, given their pivotal role in determining the energy density, cycle stability, charge/discharge rate, and safety of LBs. However, the safety concerns associated with leakage-prone and unstable electrolytes and lithium dendrites have been a significant focus of attention. Herein, an ultra-concentrated electrolyte named UC-QLi is presented, consisting of 80 wt% of a new self-conductive organic lithium bicarbonate dimethyl ammonium chloride (LiBDAC) and 20 wt% of fluoroethylene carbonate. The prepared quasi-solid electrolyte shows a high ionic conductivity (0.51 × 10−3 S cm−1) and an outstanding electrochemical stability window (above 6 V). Molecular dynamic, electron probe microanalysis, and X-ray photoelectron spectroscopy techniques have been used to investigate the potential chemical structure and formation mechanism of the solid-electrolyte-interface layer. The Li|UC-QLi|Li symmetric cell can be cycled stably at various current densities (0.5–2 mA cm−2) for 1000 h without producing lithium dendrites. The discharge capacity of the Li|UC-QLi|NCM coin cell at 0.1C reaches 164.1 mAh/g, with a Coulombic efficiency of 99 % throughout the entire cycles. The Li|UC-QLi|NCM cell can continuously and repeatedly light a commercial LED for at least 1 h without performance degradation. Most importantly, UC-QLi-based pouch cells can deliver capacity and are extremely safe. In the nail penetration test, no leakage, thermal runaway, combustion, or explosion phenomena were detected, which fully demonstrates the high safety of the real pouch cell. The herein prepared quasi-solid organic electrolyte provides a new strategy for the development of next-generation high safety LBs.